KADAR ADIPONEKTIN PLASMA PADA PASIEN YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT SANGLAH DENPASAR - Sanjaya, Surya; Suwitra, Ketut (journal of internal medicine, 2012)
Adiponectin, a cytokine with anti-inß ammatory properties that is secreted from adipose tissue. Adiponectin has been shown to be a predictor of cardiovascular events in the general population and patients who undergoing hemodialysis. The aim of this study is to evaluate serum adiponectin in patient undergoing regular hemodialysis. A cross sectional study involved 53 reguler hemodialysis patient at Sanglah hospital. Inclusion criteria was patient undergoing regular hemodialysis more than three month and twice a week. We exclude severe infections, abnormality of liver functions test, malignancies and diabetes mellitus. The mean of age and abdominal circumference was 48.01 ± 12.3 years old and 79.5 ± 9.99 cm. Systolic and diastolic blood pressure pre hemodyalisis was 140 ± 20.7 mmHg and 83.3 ± 10.7 mmHg. Systolic and diastolic blood pressure post hemodialysis was 148.6 ± 23.6 mmHg and 85.6 ± 11.5 mmHg, respectively. We found serum level of calcium 9.5 ± .97 mmol/l, inorganic phospat 6.4 ± 2.1 mmol/l, BUN 84.8 ± 19.9 mg/dl, serum creatinin 16.1 ± 3.9 mg/dl, hemoglobine levels 7.7 ± 1.4 g/dl and blood glucose levels 92.9 ± 1.4 mg/dl. Serum levels of adiponectin was 15.4 ± 5.98 mg/l compare with normal levels 5.52 mg/l. Levels of serum adiponectin in regular hemodialysis patients is three fold higher than normal population.
Keywords: hemodialysis, adiponectin